MEMAKNAI “SOLILOKUI PARA PENUNGGU HUTAN” MARHALIM ZAINI - Agus Sri Danardana (Madah: Jurnal Bahasa dan Sastra, 2016)
Sunday, February 1st 2015, Kompas published Marhalim Zaini’s (MZ) poetry, titled “Solilokui Para Penunggu Hutan”. This poetry is interesting because it is related to MZ’s oration when he was inaugurated as Seniman Pilihan Sagang 2011. In his oration, titled “Akulah Melayu yang Berlari (Percakapan-percakapan yang Tak Selesai tentang Ideologi an Identitas Kultural)”, MZ showed the problem of his identity (as a Malay). The objectives of this article are to obtain the information about what/how the content of the text and to try getting to know how and why the poetry is presented. Due to the fact that the main problem is related to MZ’s idea, thought, willingness, and/or critics of LancangKuning Land, the analysis of this article will apply structuralism theory with expressive and mimesis approach. The result shows that it is MZ’s monologue with himself in order to express his feeling, hunch, inner conflict, and/or presented the information to readers about forest dwellers. It was not done by forest dwellers, but by MZ himself about the forest dwellers. It shows that if it is related to his anxiety so far (he was accused as a convert to Islam Malay), through his poetry “Solilokui Para Penunggu Hutan”, MZ is carrying out/will carry out his self-defense.